The Dynamics of Islamic Legislation in Indonesia’s Legal Politics: A Case Study of PKS’s Rejection of The Sexual Violence Law - Elnizar, Normand Edwin; Fata, Ahmad Khoirul (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
This article analyzes the Prosperous Justice Party’s (PKS) rejection of Indonesia’s Law Number 12 of 2022 on Sexual Violence Crimes (TPKS) by examining the Islamic legal reasoning embedded in the legislative process. Using a qualitative legal research design, the study draws on parliamentary records, official party documents, and interviews with key political and religious figures to identify the normative foundations of PKS’s stance. The findings reveal that PKS frames its opposition through the preventive logic of sadd al-dzarī‘ah and selective applications of maqāṣid al-sharī‘ah, particularly hifz al-nasl and hifz al-‘ird, while giving less emphasis to victim-oriented protection associated with hifz al-nafs. The study argues that PKS’s position constitutes a form of ijtihād siyāsah dustūriyyah, in which Islamic legal principles are negotiated within constitutional legislative structures rather than articulated through traditional juristic authority. This article contributes to Islamic legal scholarship by demonstrating how partisan actors exercise Islamic legal agency within democratic institutions. It also highlights the challenges of balancing moral preservation and rights-based legal reform in a pluralistic legal system.